Structural Properties of $Rh_n (n=2$∼$100)$ Clusters by Using Gupta Potential with the Simulation of Quenching Method (Journal of Atomic and Molecular Sciences, 2013)
The ground-state geometries and energies of $Rh_n (n=2$∼$100)$ clusters are investigated by using Gupta potential combined with the molecular dynamics simulated quenching method and the genetic algorithm. Our results show that: As comparing the lowest energy structure obtained from the simulated quenching method which can be regarded as the ground-state structure, almost all these ground-state geometries can be found (except $Rh_{50})$ by using the genetic algorithm for clusters containing 60 or less atoms, but the efficiency of capturing the ground-state geometry decreases obviously with increasing the cluster size. The effective temperature range for obtaining the ground-state energy (geometry) is obtained by systematically analyzing the energy distributions of the simulated quenching structures, and the correlation between the quenching method of finding the ground-state and the cluster size is also investigated further.